Description of Organizing of Randai Activities in Sanggar Seni Sarunai Sangkokalo, Sijunjung - Zelvitu Febri Wanda; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research was motivated by the success of the Sarunai Sangkokalo Art Studio in carrying out randai activities, this was seen from the structuring of the organization carried out by the management staff in the Sarunai Sangkokalo Art Studio. The purpose of this study is to describe smart organization in terms of determining activities and personnel, delegating authority, and determining tools and infrastructure. This type of research is quantitative descriptive research. The population in this study were clever participants at the Sarunai Sangkokalo Art Studio. The sampling technique in this study is stratified random sampling of the entire population. Data collection techniques used were questionnaires, while the questionnaire data collection tools. Data analysis techniques using the percentage formula. The results of the study show that: organizing the smart activities in the Sarunai Sangkokalo Art Studio has good personnel determination and activity, as well as delegation of authority and the determination and use of tools and equipment that are good at supporting success.Keywords: Activities and Personnel, Delegates, Randai Organizing